Characterization of a remote optical element with bi-photons. (11th January 2016) - Puhlmann, D; Henkel, C; Heuer, A; Pieplow, G; Menzel, R
Abstract: We present a simple setup that exploits the interference of entangled photon pairs. 'Signal' photons are sent through a Mach–Zehnder-like interferometer, while 'idlers' are detected in a variable polarization state. Two-photon interference (in coincidence detection) is observed with very high contrast and for significant time delays between signal and idler detection events. This is explained by quantum erasure of the polarization tag and a delayed choice protocol involving a non-local virtual polarizer. The phase of the two-photon fringes is scanned by varying the path length in the signal beam or by rotating a birefringent crystal in the idler beam. We exploit this to characterize one beam splitter of the signal photon interferometer (reflection and transmission amplitudes including losses), using only information about coincidences and control parameters in the idler path. This is possible because our bi-photon state saturates the Greenberger–Yelin–Englert inequality between contrast and predictability.